The Analysis of International Tourist Streams of Ukraine for the Period from 2012 to 2017 - Глибовець, Вікторія Леонідівна; Хвесик, Юлія Михайлівна (Київський національний університет імені Тараса Шевченка, 2021)
The purpose of this article is to analyze the dynamics of tourist streams between Ukraine and other countries of the world, as well as to identify the factors that influence the development of international tourism most of all. Research methodology. The most important statistical indicators that characterize tourist streams are the number of Ukrainians who visited other countries for tourist purposes and the number of tourists - citizens of other countries, who arrived in Ukraine. In our study of the tourist streams of Ukraine the mathematical indicator that reflects the features of tourist streams and their socio-economic importance for the development of international tourism in the country, namely the coefficient of tourist exchanges, was used. Selected for the research were the countries visited by more than 50 thousand tourists from Ukraine for at least 2 years in a row. The total number of the tourists includes persons who travelled for official, tourism, and private purposes (without vehicle servicing personnel and servicemen). Results of the research. Most tourists from Ukraine go to neighboring countries, namely to Russia, Moldova, Belarus, Poland, Romania, Hungary, and Turkey. Turkey is a popular holiday destination among Ukrainians, because it's close to Ukraine and can provide tourists with a good service. It is necessary to take into account the fact that a large number of Ukrainians work abroad, mainly in Europe, as well as in Russia. When these people leave for a foreign country, they can state their visit is private, not working; therefore, they are mistakenly defined as tourists. The donor countries of tourists who come to Ukraine are (the coefficient tends to "1") Tajikistan, Uzbekistan, and the United States. The countries for which Ukraine is a donor of tourists are the (coefficient tends to "-1") United Arab Emirates, Egypt, Cyprus, Spain, Greece, Austria, Turkey, and Poland. Scientific novelty. For the first time, the coefficient of tourist exchanges of Ukraine in relation to 29 countries of the world for 2012 and 2017 was calculated. The donor countries of tourists coming to Ukraine, as well as the countries for which Ukraine is a donor of tourists were identified. Practical significance. It is to reveal the fact that Ukraine is a donor country for tourists. Given the fact that Ukraine is rich in tourist resources, over time, using the experience of tourist countries around the world, it can change this status and receive more foreign tourists.

Метою статті є аналіз динаміки туристичних потоків між Україною та іншими країнами світу, а також виявлення чинників, які найбільше впливають на розвиток міжнародного туризму. Методика дослідження. Найважливішими статистичними показниками, що характеризують туристичні потоки, є кількість українців, які відвідали інші країни з туристичною метою та кількість туристів - громадян інших країн, які прибули до України. У нашому дослідженні туристичних потоків України був використаний математичний показник, що відображає особливості туристичних потоків та їх соціальноекономічне значення для розвитку міжнародного туризму в країні, а саме коефіцієнт туристичних обмінів. Для дослідження були обрані країни, які принаймні 2 роки поспіль відвідували понад 50 тисяч туристів з України. Загальна кількість туристів включає осіб, які подорожували зі службовими, туристичними та приватними цілями (не враховуючи обслуговуючий персонал та військовослужбовців). Результати дослідження. Більшість туристів з України їдуть до сусідніх країн, а саме до Росії, Молдови, Білорусі, Польщі, Румунії, Угорщини та Туреччини. Туреччина є популярним місцем відпочинку серед українців, оскільки знаходиться недалеко від України і може надати туристам хороший сервіс. Необхідно врахувати той факт, що велика кількість українців працює за кордоном, переважно в Європі, а також у Росії. Коли ці люди виїжджають до іноземної країни, вони можуть заявити, що їх візит є приватним, а не робочим; тому їх помилково визначають як туристів. Країнами-донорами туристів, які приїжджають в Україну, є (коефіцієнт має тенденцію до «1») Таджикистан, Узбекистан та США. Країнами, для яких Україна є донором туристів, є (коефіцієнт має тенденцію до «-1») Об'єднані Арабські Емірати, Єгипет, Кіпр, Іспанія, Греція, Австрія, Туреччина та Польща. Наукова новизна. Вперше розраховано коефіцієнт туристичних обмінів України по відношенню до 29 країн світу за 2012 та 2017 роки. Виявлено країни-донори туристів, що приїжджають до України, а також країни, для яких Україна є донором туристів. Практична значимість. Полягає у виявленні того факту, що Україна - це країна-донор туристів. Враховуючи той факт, що Україна багата на туристичні ресурси, з часом, використовуючи досвід туристичних країн світу, вона може змінити цей статус і приймати більше іноземних туристів.
Аналіз міжнародних туристичних потоків України за період з 2012 по 2017 рік
Keywords: туристичні потоки; коефіцієнт туристичних обмінів; донори туристів; tourist streams; the coefficient of tourist exchanges; donors of tourists